Factors Related to Compliance in the Implementation of Clinical Pathway by Health Workers in the Treatment Room of Benjamin Guluh Hospital, Kolaka Regency - Yulianti, Yuni; Saafi, La Ode; Saltar, La Ode (Waluya The International Science of Health Journal, 2024)
Introduction: The problem of the implementation of the clinical pathway at Benyamin Guluh hospital is the lack of compliance of health workers in carrying out services in accordance with the clinical pathway format. This study aims to analyze factors related to compliance in the implementation of clinical pathways by health workers in the treatment room of Benyamin Guluh Hospital, Kolaka Regency. Method: Quantitative research with a cross sectional study approach. The population of this study is 151 people, with a sample of 110 people. Sample withdrawal uses cluster random sampling. Data collection uses questionnaires and data from agencies related to the research. Data analysis using chi square test. Result: The results of the study obtained the variable of work commitment (X2count = 12,332 > X2table = 3,841 and Phi (j) = 0,335), communication (X2count = 12,463 > X2table = 3,841 and Phi (j) = 0,337), knowledge (X2count = 10,876 > X2table = 3,841 and Phi (j) = 0,314), and attitude (X2count = 8,759 > X2table = 3,841 and Phi (j) = 0,282). Conclusion: There is a moderate relationship between work commitment, communication, knowledge, and attitude and compliance in the implementation of clinical pathways by health workers in the treatment room of Benjamin Guluh Hospital, Kolaka Regency.